Design and thermodynamic analysis of a combined system including steam Rankine cycle, organic Rankine cycle, and power turbine for marine low-speed diesel engine waste heat recovery. (1st October 2021) - Qu, Jinbo; Feng, Yongming; Zhu, Yuanqing; Zhou, Song; Zhang, Wenping
Highlights: A waste heat recovery system is proposed including power turbine, steam Rankine cycle and organic Ranking cycle. An optimal design on system is carried out, which is verified by tests. The thermodynamic analysis and techno-economic evaluation are performed. An improved system is proposed to solve the problem from designed system. Abstract: In the current global decarbonization energy background of carbon peak emissions and carbon neutralization, more and more attention has been paid to the research of improving the energy efficiency of marine power plants. The thermal cycle device is used to recover the waste heat of marine diesel engines and reduce carbon emissions. Therefore, a set of high-efficiency waste heat recovery systems including power turbine (PT), steam Rankine cycle (RC), an organic Rankine cycle (ORC) is designed and tested. The test results showed that the designed system ran stably. Then, according to the test results, the system was further calculated. The calculation results showed that it is possible to generate power up to 1, 079.1 KW at 100% load utilizing this system. Besides, the maximum thermal efficiency and exergy efficiency of the RC-ORC unit occurred at 90% load, which were 28.48% and 65.72% respectively. Furthermore, the techno-economic evaluation was carried out. The results show that the payback period and the depreciation payback period of this system are 5.2 years and 6.9 years, respectively. Finally, the system was improved, the coupling degree of RC-ORC was reduced, and the reliability and stability of the system were improved on the premise that little power generation ratio increased at high load and slight decreased at low load.